Description Of Nurse Compliance Level Inimplementing Covid-19 Health Protocols In The Treatment Rooms Of Santa Elisabeth Hospital In 2021 - Lindawati Simorangkir; Pomarida Simbolon; Frekdijon Situmorang (Sean Institute, 2023)
Covid 19 has become a pandemic disease in 2019, where handling and prevention can be carried out by paying attention to health protocols. The reason for this is due to a lack of adherence to the importance of the covid 19 health protocol. This research uses descriptive analytic method. Sampling technique usingrandom samplingwith a total sample of 25 respondents. Measuring tool used in the form of a questionnaire. Based on the results of the data analysis carried out, it was found that there was an overview of the level of compliance of nurses in implementing the Covid 19 health protocol with the implementation of 3M, namely washing hands, using masks and keeping a distanceit was found that 59 (88.1%) were classified as obedient. The level of nurse compliance in implementing the Covid-19 health protocol.It is hoped that this can be information for all employees of the Santa Elisabeth Medan Hospital in identifying compliance in implementing the Covid-19 health protocol both within the hospital and outside the hospital.